Impact of Inverter Control and Solar Photovoltaic Integration on Small Signal Stability Augmented with Battery: Modal Analysis Approach (MIST International Journal of Science and Technology, 2025)
The increasing penetration of renewable energy sources, particularly solar photovoltaic (PV), poses significant challenges to grid stability due to the reduction in system inertia. This paper evaluates three inverter control strategies -Vac-Φ,Vac-P and P-Q-using modal analysis and participation matrix evaluation to identify the most effective approach for enhancing small signal stability. Among these, the P-Q control strategy emerges as the best-performing technique, with a notable eigenvalue improvement from -O. 62+9.607i (Vac-Φ) to -14.79 +0.668i , achieving an exceptionally high damping ratio of 0.998. The participation matrix analysis highlights the dominance of active power control in stabilizing critical modes, further validating the superior performance of P-Q control. Moreover, the impact of solar PV has been demonstrated and enhancement of system stability utilizing Battery Energy Storage System (BESS) has been shown in this paper.MIJST, V. 13, December 2025: 73-84https://doi.org/10.47981/j.mijst.13(02)2025.527(73-84)